Potensi Tradisi Nyorong Sebagai Konteks Pembelajaran IPA Kontekstual Berbasis Budaya Lokal: Tinjauan Literatur - Siska Afrilianti; Asyil Arifah; Eldza Rosmiatin Nafis (Indonesian Publication Center, 2026)
Science education in the Merdeka Curriculum calls for a contextual and meaningful approach, yet science instruction often remains abstract and lacks a connection to students’ real-life experiences. An ethoscience approach can offer a solution by integrating local community knowledge into scientific concepts. However, studies that specifically map the Nyorong tradition of the Samawa tribe into school science concepts particularly in the physics topics of work and energy remain limited. This review article aims to analyze the potential of the Nyorong tradition as a context for contextual, ethnoscience-based science learning by mapping cultural activities to the concepts of work and energy. The study employed a narrative review method, examining 16 selected articles retrieved from the Google Scholar, ScienceDirect, ERIC, SpringerLink, and Garuda databases between 2021 and 2026. Data were analyzed using content analysis through thematic grouping and synthesis of findings. The results indicate that the Nyorong tradition includes activities relevant to the concepts of force, work, potential energy, kinetic energy, energy transformation, and power. Integrating the Nyorong tradition has the potential to enhance science literacy, scientific process skills, the relevance of learning, as well as the instillation of character values and appreciation for local culture. This study contributes to enriching references for local culture-based science education and opens opportunities for the development of contextual teaching materials in secondary schools.